2021
DOI: 10.1088/1755-1315/911/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Acid soil tolerance of 28 soybean varieties in hydroponics and soil-based evaluation

Abstract: Utilization of marginal soil plays important role in improving soybean production in Indonesia. Soybean breeding program targeting high yielding varieties and tolerant to acid soils is estimated to be more cost-effective and environmentally friendly approach in improving plant productivity on acid soil. The aim of this research was to study plant response under acid soil stress and to identify tolerant and sensitive genotype which might be useful for further breeding program. The experiment was conducted using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Furthermore, we wanted to identify soybean genotypes that are acid tolerant and produce good nutritional content. In a preliminary study, Puspitasari et al (2021) reported that soil with pH 4.0 would result in shorter plants, and fewer branches and nodes compared to pH 5.4 (p < 0.05). In contrast, Nadeem et al (2019) reported that acidic soils (6.0 and 5.1) could enhanced forage production (38% and 39%, respectively) of soybean compared to soil of pH 6.8.…”
Section: Correlationmentioning
confidence: 96%
See 3 more Smart Citations
“…Furthermore, we wanted to identify soybean genotypes that are acid tolerant and produce good nutritional content. In a preliminary study, Puspitasari et al (2021) reported that soil with pH 4.0 would result in shorter plants, and fewer branches and nodes compared to pH 5.4 (p < 0.05). In contrast, Nadeem et al (2019) reported that acidic soils (6.0 and 5.1) could enhanced forage production (38% and 39%, respectively) of soybean compared to soil of pH 6.8.…”
Section: Correlationmentioning
confidence: 96%
“…However, there are several soybean genotypes that are tolerant of Al toxicity and can maintain nutritional quality (Kang et al, 2011). Demas 1 was released as a genotype tolerant of acid soil and experimental results for soybean yields strengthen the view of Demas 1 as tolerant genotype (Puspitasari et al, 2021).…”
Section: Correlationmentioning
confidence: 99%
See 2 more Smart Citations